Weak base pretreatment on coconut coir fibers for ethanol production using a simultaneous saccharification and fermentation process. Issue 3 (16th March 2021) - Ebrahimi, Majid; Caparanga, Alvin R.; Villaflores, Oliver B.
ABSTRACT: In this work, coconut coir fibers, which are a good source of lignocellulosic biomass with a composition of 34.80% glucan, 18.30% xylan, 35.80% lignin and 8.70% extractives, were successfully pretreated with ammonium carbonate solution (20 and 25 wt.%) at 80°C for 4, 8 and 12 h working time at laboratory scale. The maximum yield of enzymatic hydrolysis (glucan digestibility) after 8 h was 77.03% and 71.43% after the 20% and 25% ammonium carbonate pretreatment, respectively. The simple simultaneous saccharification and fermentation (SSF) process was anaerobically carried out in order to produce second-generation bioethanol from coconut coir fibers at 37°C. The SSF slurry contained Saccharomyces cerevisiae yeast, 5% w/v glucan (untreated and pretreated samples), and 10 FPU/g glucan of cellulase. Subsequently, the maximum ethanol concentration was 8.65 g/L, after 72 h incubation, from 20% ammonium carbonate pretreated biomass for 8 h.